Calculation of Fire Resistance Range of Bending Reinforcement Constructions in Non-Dimensional Parameters - G. I. Kasperov; I. I. Palevoda (Наука и техника)
The paper presents the method that makes it possible to calculate fire resistance of bending reinforcement constructions in the case when concrete and reinforcement classes are unknown. The method is recommended to substantiate a conclusion in field of fire safety made by experts of the State Fire Supervision Committee.